2023
DOI: 10.1097/md.0000000000032928
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of cell-free DNA in thyroid cancer: A systematic review and meta-analysis

Abstract: Objective: An increasing number of studies have shown the potential diagnostic value of cell-free DNA (cfDNA) as a new biomarker in the management of thyroid cancer (TC); however, the accuracy of research results is inconsistent. This meta-analysis is the first to synthesize published results and evaluate the application value of circulating cfDNA in the diagnosis of TC.Methods: A search strategy was developed according to PICO (P: Patient; I: Intervention; C: Comparison; O: Outcome) principles. We searched 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Previous meta‐analyses on the diagnostic accuracy of quantitative cfDNA testing demonstrated that this technology is better than conventional biomarkers for several cancer diagnoses including gastric cancer, 42 lung cancer, 43 thyroid cancer, 44 HN cancer, 45 and colon cancer 46 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous meta‐analyses on the diagnostic accuracy of quantitative cfDNA testing demonstrated that this technology is better than conventional biomarkers for several cancer diagnoses including gastric cancer, 42 lung cancer, 43 thyroid cancer, 44 HN cancer, 45 and colon cancer 46 …”
Section: Discussionmentioning
confidence: 99%
“…Included studies fulfilled the items "patient selection," "index test," "reference standard," and "flow and timing" of the risk of the bias section and all three items of the applicability concerns section ("patient selection," "index test," and "reference standard"). Previous meta-analyses on the diagnostic accuracy of quantitative cfDNA testing demonstrated that this technology is better than conventional biomarkers for several cancer diagnoses including gastric cancer, 42 lung cancer, 43 thyroid cancer, 44 HN cancer, 45 and colon cancer. 46 To the best our knowledge, this is the first metaanalysis exploring the accuracy of ctHPVDNA by ddPCR in patients at diagnosis of HPV + OPSCC.…”
Section: Qualitative Assessmentmentioning
confidence: 99%
“…On the other hand, there are non-specific biomarkers evaluated for refining the diagnosis of indeterminate thyroid nodule such as the quantification of cfDNA or cfDNA fragmentation index 85 , 86 . In the recent meta-analysis by Hou 87 and colleagues all these biomarkers were debated. They found that a combination of multiple cfDNA biomarkers may be more accurate than single biomarker testing.…”
Section: Liquid Biopsymentioning
confidence: 99%